UPAYA MENINGKATKAN LAYANAN JASA DAN MENURUNKAN CUSTOMER COMPLAIN MENGGUNAKAN METODE FUZZY- SERVQUAL DI PT. EUROTRANS CHARTER INDONESIA - Febri Yanti; Ariya Purnamasari Dewi (Spektrum Industri, 2017)
PT. Eurotrans Charter Indonesia Fowarding Freight is a company engaged in the transportation services that keep in touch with customers. In the development of its PT. Eurotrans Charter Indonesia decreased its shipment (number of document processing requests). To keep keeksistensianya PT. Eurotrans Charter Indonesia Need to maintain the quality of ministry. Thus the need for a method to measure the quality of service PT. Eurotrans Charter Indonesia and the need to improve the quality of services provided so that customers feel comfortable and satisfied so that it can survive to compete with competitors PT Forwarding lainnya.Langkah-steps involved in data collection is done by observation and questionnaires from several criteria. Those criteria obtained through interviews and studies pustaka..Metode used to measure the quality of service using Fuzzy Servqual. The results of data processing, found that the value of fuzzy-servqual per criteria, perdimensi and overall By using 5 Dimensions in servqual namely: direct evidence (Tangibles), Reliability (Reliability), Responsiveness (Responsiveness), Security (Assurance), Empathy (Empathy). After measuring the quality of service PT. Eurotrans Charter Indonesia found the results showed that customers' expectations have not been in accordance with the perception of the services they receive. Results gap of -1.06 and therefore the management of PT. Eurotrans Charter of Indonesia needs to make improvements of service quality for the sake of reducing the existing gap. To make improvements to the company made by using analysis 5W1H (what, why, when where, who and how) .After note 5 biggest gap in ": Various complete facilities provided by the management, .Kemudahan in payment processing, support services revision PT. Eurotrans Charter Indonesia do a double check and do not make mistakes in working document. quotation (supply) that is given an interesting, and hospitality employees to customers, After the PT. Eurotrans Charter Indonesia improve by 5 w 1h and managed by lowering the number of customer complaints were received PT. Eurotrans Charter Indonesia that before the repair amounts to average number of customers complain - 4 Average monthly customer complaints after the transactions are carried out repairs down menejadi two customer complaints per monthKeyword: Fuzzy Servqual Service, perceptions, expectations